Energy-Efficient Air Conditioning : A Case Study of the Maghreb - Khalfallah, Ezzedine; Missaoui, Rafik; El Khamlichi, Samira; Ben Hassine, Hassen (World Bank, Washington, DC, 2016)
Four countries in the Maghreb region of North Africa — Algeria, Libya, Morocco, and Tunisia are facing the common challenge of a rapid increase in energy demand, in particular for electricity, linked to population growth and rising standards of living. Peak demand in these countries has increased in recent years, at an estimated average of 6 percent annually between 2004 and 2013. Electricity generation capacity has been ramped up significantly each year to cope with this rapid increase in demand. It is estimated that the Maghreb will need to double its installed generation capacity by 2020 if it is to keep pace with the rising demand. This study focuses on four countries of the Maghreb, namely Algeria, Morocco, Tunisia, and Libya. However, given the political situation and the lack of information in Libya, the analyses are often confined to three countries: Algeria, Morocco, and Tunisia. This report is divided into six sections that focus on the following topics: 1) Energy challenges facing the Maghreb; 2) Overview of air-conditioning systems in the region; 3) Analysis of the current market; 4) Outlook on market developments and challenges; 5) Policies, measures, and tools to enhance energy efficiency; and 6) Recommendations for transforming the air-conditioning market in the Maghreb—a way forward.